The impact of board attributes and insider ownership on corporate cash holdings: Evidence from Pakistan - Nadeem Ahmed Sheikh; Muhammad Imran Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The purpose of this paper is to investigate the impact of board attributes and insider ownership on cash holdings of non-financial firms listed on Karachi Stock Exchange (KSE) Pakistan during 2008-2012. Empirical results indicate that board attributes such as CEO duality, board size and board independence are positively related to cash holdings. However, board independence is the only boards attribute which is found statistically significant. The insider ownership is significantly and negatively related to cash holdings. Alternatively, the square of insider ownership is significantly and positively related to cash holdings. The variation in signs indicates a non-linear relationship. Notably, sample firms are divided into three insider ownership structures i.e. family firm, pyramid firm and non-family firm. Results indicate that family firm is negatively while non-family firm is positively related to cash holdings. These findings indicate that family firms prefer to hold necessary amount of cash enough for their planned as well as unplanned payments than non-family firms. On the other hand, pyramid firm is positively related to cash holdings but the relationship is insignificant. In summary, empirical results indicate that board attributes and insider ownership are important predictors of corporate cash holdings for non-financial firms in Pakistan.
Keywords: 330; board independence; board size; CEO duality; cash holdings; family-firm; insider ownership; non-family firm; pyramid firm